The ecology of medical care in Korea: the association of a regular doctor and medical care utilization - Jeehye Lee; Yong-jun Choi; Dong-Hee Ryu (BMC, 2022)
Abstract Backgrounds There is no registered regular doctor system in Korea, but people voluntarily select regular doctors for medical services. This study aims to study the ecology of medical care in Korea according to the presence and type of a regular doctor. Methods This study was conducted using Korean Health Panel survey in 2018. The proportion of people who had health problems and received medical care in various settings was analyzed per 1,000 people according to the following groups: without a regular doctor, having a clinic physician as a regular doctor, and having a hospital physician as a regular doctor. The adjusted odds ratio for usage of medical services was calculated. Results Health problems and medical care use increased in the groups in this order: group without a regular doctor, group with a clinic physician as a regular doctor, the group with a hospital physician a regular doctor. Having a hospital physician as a regular doctor was associated with higher odds of inpatient care and emergency room visits, and having a clinic physician as a regular doctor was not associated with odds of inpatient care and emergency room visits when adjusting demographic and health-related variables. Conclusion Depending on whether having a regular doctor and a regular doctor's type, different ecology of medical care was observed. The position and role of a regular doctor in the context of the Korea health care system should be considered from the perspective of primary care.